Effects of returning peach branch waste to fields on soil carbon cycle mediated by soil microbial communities - Liu, Chenyu; Liu, Zhiling; Cui, Bofei; Yang, Haiqing; Gao, Chengda; Chang, Mingming; Liu, Yueping (Frontiers in Microbiology, 2024)
In recent years, the rise in greenhouse gas emissions from agriculture has worsened climate change. Efficiently utilizing agricultural waste can significantly mitigate these effects. This study investigated the ecological benefits of returning peach branch waste to fields (RPBF) through three innovative strategies: (1) application of peach branch organic fertilizer (OF), (2) mushroom cultivation using peach branches as a substrate (MC), and (3) surface mulching with peach branches (SM). Conducted within a peach orchard ecosystem, our research aimed to assess these resource utilization strategies' effects on soil properties, microbial community, and carbon cycle, thereby contributing to sustainable agricultural practices. Our findings indicated that all RPBF treatments enhance soil nutrient content, enriching beneficial microorganisms, such as Humicola, Rhizobiales, and Bacillus. Moreover, soil AP and AK were observed to regulate the soil carbon cycle by altering the compositions and functions of microbial communities. Notably, OF and MC treatments were found to boost autotrophic microorganism abundance, thereby augmenting the potential for soil carbon sequestration and emission reduction. Interestingly, in peach orchard soil, fungal communities were found to contribute more greatly to SOC content than bacterial communities. However, SM treatment resulted in an increase in the presence of bacterial communities, thereby enhancing carbon emissions. Overall, this study illustrated the fundamental pathways by which RPBF treatment affects the soil carbon cycle, providing novel insights into the rational resource utilization of peach branch waste and the advancement of ecological agriculture.